Mobilisasi Sosial Peserta Didik Dalam Lembaga Pesantren - Irmawati, Irmawati; Mukramin, Sam'un (Pascasarjana IAIN Metro, 2023)
Islamic boarding schools still exist in the world of education and empowerment in Indonesia. However, in its journey, Islamic education often separates students from their social life. This happens because the Islamic education provided is no longer based on the social reality of society. Public's distrust of the ability of religious education institutions to guarantee the future is a very concerning phenomenon. This can be seen from the fact that the number of students enrolling their children in general educational institutions is still much higher than that of children enrolling in religious education institutions. Type of research used is qualitative with a library research design or literature method. The literature method is method by collecting, identifying, and processing written data obtained and can be used as input in the analysis process. Meanwhile, data analysis was carried out using research results that were sequentially considered from the most relevant, relevant, and quite relevant. as well as seeing the year of research starting from the most recent, and gradually moving backwards to a longer year.Results of this study can be concluded that religious education institutions, especially education at Islamic boarding schools is an effective and efficient path and is open to anyone.